Children's reading and writing success: the role of diligence and intelligence. (2015) - Briggs, Teinye; Ololube, Nwachukwu Prince
In today's world, young children look for attention and engage in positive or negative behaviour to attain it and it is important that teachers recognise the diligence and intelligence worth of their students on a consistent basis. This study posits two constructs: diligence and intelligence, which express or reflect individual children's efforts towards achieving reading and writing success. A Diligence and Intelligence Inventory was developed with assistance from experts to elicit data from 6-, 7- and 8-year-old children's teachers on their pupils' achievements in reading and writing. Using Cronback analysis and construct validation procedures, the instrument was certified to have internal consistency. The results from 321 preschool children revealed a significant statistical difference between diligence and intelligence. Thus, both diligence and intelligence are not singing from the same hymnbook. The academic and practical implications of this study to educational practice include a greater need to complement the efforts of young children in their pursuit for balanced educational development.